Phase I studies of the safety, tolerability, pharmacokinetics, and pharmacodynamics of DS‐1211, a tissue‐nonspecific alkaline phosphatase inhibitor - Sonomi Maruyama; Hester Visser; Takashi Ito; Tharin Limsakun; Hamim Zahir; Daniel Ford; Ben Tao; Cynthia A. Zamora; Jeffrey G. Stark; Hubert S. Chou (Wiley, 2022)
Abstract Tissue‐nonspecific alkaline phosphatase (TNAP) hydrolyzes and inactivates inorganic pyrophosphate (PPi), a potent inhibitor of calcification; therefore, TNAP inhibition is a potential target to treat ectopic calcification. These two first‐in‐human studies evaluated safety, tolerability, pharmacokinetics (PKs), and pharmacodynamics (PDs) of single (SAD) and multiple‐ascending doses (MAD) of DS‐1211, a TNAP inhibitor. Healthy adults were randomized 6:2 to DS‐1211 or placebo, eight subjects per dose cohort. SAD study subjects received one dose of DS‐1211 (range, 3-3000 mg) or placebo, whereas MAD study subjects received DS‐1211 (range, 10-300 mg) once daily, 150 mg twice daily (b.i.d.), or placebo for 10 days. Primary end points were safety and tolerability. PK and PD assessments included plasma concentrations of DS‐1211, alkaline phosphatase (ALP) activity, and TNAP substrates (PPi, pyridoxal 5'‐phosphate [PLP], and phosphoethanolamine [PEA]). A total of 56 (DS‐1211: n = 42; placebo: n = 14) and 40 (DS‐1211: n = 30; placebo: n = 10) subjects enrolled in the SAD and MAD studies, respectively. In both studies, adverse events were mild or moderate and did not increase with dose. PKs of DS‐1211 were linear up to 100 mg administered as a single dose and 150 mg b.i.d. administered as a multiple‐dose regimen. In multiple dosing, there was minimal accumulation of DS‐1211. Increased DS‐1211 exposure correlated with dose‐dependent ALP inhibition and concomitant increases in PPi, PLP, and PEA. In two phase I studies, DS‐1211 appeared safe and well‐tolerated. Post‐treatment PD assessments were consistent with exposure‐dependent TNAP inhibition. These data support further evaluation of DS‐1211 for ectopic calcification diseases.